Pelatihan Kepatuhan Koperasi Terhadap Penyelenggaraan Pengembangan dan Penguatan Sektor Keuangan : Bagi Pengurus dan Pengawas Koperasi di Provinsi Jawa Barat Dengan Klasifikasi Koperasi Simpan Pinjam dan Koperasi yang Memiliki Unit Usaha Simpan Pinjam - Dandan Irawan (LPPM Universitas Koperasi Indonesia, 2023)
Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Services Sector (UU PPSK) is the initiative of the Government and the DPR to advance public welfare by reforming the Indonesian financial sector. Compromises for Savings and Loans (KSP) and Savings and Loan Units (USP) operations are divided into closed loops where KSP and USP are supervised by the Ministry of Cooperatives and of course, internal cooperatives and opened loop for KSP and given a two-year transition period to become a Financial Services Cooperative supervised by the Financial Services Authority (OJK). This study recommends that the regulation and supervision of cooperative savings and loan business activities be more suitable for the Government on the grounds of the context of cooperative development, democracy, social inclusion, local culture, history, regulation, and taking into account lessons learned experiences of other countries in developing cooperatives. While the regulation and supervision of financial services businesses by cooperatives is more suitable to be supervised by the OJK on the grounds that financial service cooperatives can raise public funds and protect consumers who use financial services. The PPSK Bill contains a number of articles on technical matters that should be sufficiently regulated in the PP. The PPSK Bill needs to accommodate the voices and aspirations of the cooperative movement aimed at encouraging the growth of supporting institutions needed by KSP/USP and Financial Services Cooperatives. Methods Training is carried out using a participatory method that allows participants to interact directly with the trainers/instructors